2004
DOI: 10.1016/s0966-6362(03)00071-7
|View full text |Cite
|
Sign up to set email alerts
|

Speed related changes in muscle activity from normal to very slow walking speeds

Abstract: Speed related changes in muscle activity from normal to very slow walking speeds den Otter, Rob; Mulder, T.; Duysens, J. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical reasons the number of authors shown on this cover page is limited to 10 maximum. Abst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
150
2
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(201 citation statements)
references
References 25 publications
31
150
2
4
Order By: Relevance
“…This study confirms, as others have shown, that the TA and the VL are active during the expected phases of the gait cycle. 7,8,31 The change in fascicle length provides insight into the dynamics of muscle function and inferences can be made concerning the interaction between muscle fascicle and tendon length change during different phases of the gait cycle.…”
Section: Vastus Lateralismentioning
confidence: 99%
“…This study confirms, as others have shown, that the TA and the VL are active during the expected phases of the gait cycle. 7,8,31 The change in fascicle length provides insight into the dynamics of muscle function and inferences can be made concerning the interaction between muscle fascicle and tendon length change during different phases of the gait cycle.…”
Section: Vastus Lateralismentioning
confidence: 99%
“…Numerosos autores han estudiado la influencia de la velocidad en los parámetros espaciotemporales y cinemáticos, determinando cuáles son los cambios que se producen en la marcha humana durante una velocidad lenta (Beauchet et al, 2009;Bejek et al, 2006;Chiu, Wu, & Chang, 2013;Chung, & Wang, 2010;Den Otter, Geurts, Mulder, & Duysens, 2004;Hirasaki, Moore, Raphan, & Cohen., 1999;Jordan, Challis, & Newell, 2007;Kang, & Dingwell, 2007;Kavanagh, 2009;Nymark et al, 2005;Orendurff et al, 2004;Pépin et al, 2003a;Pépin et al, 2003b;Shemmell, Johansson, Portra, Gottlieb, Thomas, & Corcos, 2007;Swinnen et al, 2013;Tanawongsuwan, & Bobick, 2003;Tesio et al, 1998;Thomas, De Vito, & Macaluso, 2007;Yoon, Park, & Damiano, 2012). La cadencia y longitud de paso o longitud de zancada, directamente relacionados con la velocidad, disminuyen de forma paralela a la velocidad (Bejek et al, 2006;Kirtley, 2006;Riley et al, 2001;Shemmell et al, 2007;Tanawongsuwan, & Bobick, 2003), mientras que el ancho de paso se incrementa para dar mayor base de sustentación (Ordendurff et al, 2004).…”
Section: Otros Factores Que Modifican El Patrón De La Marchaunclassified
“…Poniendo de manifiesto los cambios en el patrón de la marcha como consecuencia de una disminución de la velocidad, resulta importante el estudio de los patrones de la marcha con sujetos sanos y la creación de bases de datos a velocidades lentas con el objetivo de poder disociar las modificaciones del patrón normal relativas a las patologías neuromusculoesqueléticas de las adaptaciones producidas por la velocidad (Den Otter et al, 2004;Nymark et al, 2005). Además, estas bases de datos debieran estar diseñadas para cada una de las velocidades elegidas en cada una de las patologías.…”
Section: Otros Factores Que Modifican El Patrón De La Marchaunclassified
“…Previous studies did not show a clear effect of walking speed on EMG-EMG (Hansen et al, 2005;den Otter et al, 2004) or EEG-EMG (Petersen et al, 2012) coherence. In accordance with these studies we also observed no influence of walking speed on the coherence variables.…”
Section: Variablesmentioning
confidence: 99%
“…TA is active during the complete swing phase, which lasts from approximately 60% − 100% of the gait cycle (where 0 and 100% indicate heel strike of the concerned leg). As the timing of this muscle's burst is similar across the walking speeds used in this study (den Otter et al, 2004), we selected for every step the segment between 60% and 100% of the gait cycle. Although the TA activity extends into the stance phase, we did not use this data to exclude any possible heel strike artefacts from the analysis (Petersen et al, 2010).…”
Section: Intramuscular Coherence Analysismentioning
confidence: 99%